Circular RNA circ0007360 Attenuates Gastric Cancer Progression by Altering the miR-762/IRF7 Axis - Xing, Yawei; Chen, Hongxia; Guo, Zixiang; Zhou, Xiaodong (Frontiers in Cell and Developmental Biology, 2022)
Gastric cancer is a major health burden worldwide. Circular RNAs (circRNAs) are a novel family of noncoding RNAs that are involved in the progression of diverse types of cancers, including gastric cancer. Our present study focused on the role of circ0007360 in the progression of gastric cancer, as the biological functions and molecular mechanisms of this newly identified circRNA have not been investigated. After characterizing circ0007360 as a cytoplasmic circRNA, we observed the inhibitory effects of circ0007260 on the survival, migration, invasion, and stemness of gastric cancer cells. Next, miR-762 was identified as a direct target microRNA (miRNA) of circ0007360 and proved to act as a vital downstream molecule to fulfill the tumor-promoting effects when circ0007360 was silenced. Furthermore, we found that interferon regulatory factor 7 (IRF7), which was validated as a target gene of miR-762, served as an indirect target of circ0007360 to attenuate the progression of gastric cancer. Moreover, in vivo experiments confirmed the potentiation of gastric cancer cell growth and stemness upon depletion of circ0007360. In summary, our results revealed that the modulation of the circ0007360/miR-762/IRF7 axis is a novel mechanism for the attenuation of gastric cancer progression. Our study may shed light on the diagnostic and therapeutic value of circ0007360 in patients with gastric cancer.